Bridges and barriers: globalisation and the mobility of work and workers. (1st October 2012) - Ursula Huws
Abstract : This article starts by discussing the global division of labour. To what extent can its spatial patterns be explained by simple economic logic and to what extent is it shaped by specific features of national and local environments and corporate strategies? What factors enable restructuring, and what are the barriers to the mobility both of capital and of labour? It then introduces the articles in this issue, which display the complexity of global value chain restructuring and the ways in which it differs from popular stereotypes, as well as the common patterns that emerge. They show that restructuring is generally an incremental process, rather than a one-off change, involving mutual adaptation and accommodation to local institutional and labour market contexts. These articles do not just explore the degree to which workers consent, or resist, these changes but also look at the impacts of these decisions on the subsequent careers of those who are drawn into new positions in the global division of labour and those who are left behind.